PENGARUH PENERAPAN PRICE LIMIT DAN TRADING HALT TERHADAP VOLATILITAS RETURN DAN PEMBENTUKAN HARGA DI BURSA EFEK INDONESIA TAHUN 2020 - Rizky Utami, Anindya; Mawardi, Wisnu (Diponegoro Journal of Management, 2021)
The purpose of this study is to examine the effect of two trading mechanisms on the Indonesia Stock Exchange, namely price limit and trading halt on return volatility and price discovery during the Covid-19 Pandemic in 2020. Return volatility is measured using the daily returns-squarer Meanwhile, the price discovery measured by price behavior and return behavior. This study uses secondary data from daily historical stock prices on the Indonesia Stock Exchange for the period 2020. Based on the purposive sampling method, this study acquired 48 stock samples. The results show that the price limit has a negative effect on return volatility. The trading halt has a positive effect on return volatility. Meanwhile, price limit and trading halt have a negative effect on the price formation process. The results of this study also show that halt trading performance is more effective than price limit in terms of its ability to reduce stock return volatility